2013
DOI: 10.1017/s0007114513000627
|View full text |Cite
|
Sign up to set email alerts
|

Insulinotropic and β-cell protective action of cuminaldehyde, cuminol and an inhibitor isolated from Cuminum cyminum in streptozotocin-induced diabetic rats

Abstract: Cuminum cyminum, a commonly used spice, is known to have anti-diabetic action. The present study aims towards the isolation of bioactive components from C. cyminum and the evaluation of their insulin secretagogue potential with the probable mechanism and β-cell protective action. The anti-diabetic activity was detected in the petroleum ether (pet ether) fraction of the C. cyminum distillate and studied through in vivo and in vitro experiments. Bioactive components were identified through GC-MS, Fourier transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 30 publications
1
41
0
1
Order By: Relevance
“…Cuminaldehyde and cuminol, secondary metabolites from C. cyminum L. showed 3.34-and 3.85-fold increase in insulin secretion, respectively, in diabetic rat model (Patil et al, 2013).…”
Section: Previous Studies On Mentioned Herbal Remedies For Diabetes Mmentioning
confidence: 87%
“…Cuminaldehyde and cuminol, secondary metabolites from C. cyminum L. showed 3.34-and 3.85-fold increase in insulin secretion, respectively, in diabetic rat model (Patil et al, 2013).…”
Section: Previous Studies On Mentioned Herbal Remedies For Diabetes Mmentioning
confidence: 87%
“…Later, Patil et al [20] 2013 showed that cuminaldehyde had glucose dependent insulinotropic effects in diabetic rats, an effect which was found to be mediated through blocking ATP sensitive potassium channels and increasing intracellular calcium concentration in cultured rat pancreatic cells. Moreover, cuminaldehyde protected pancreatic β cells against cytotoxicity induced by streptozotocin [20].…”
Section: Antidiabetic Effects Of Cuminaldehydementioning
confidence: 99%
“…But in another study performed on overweight subjects, no meaningful effect of C. cyminum on plasma glucose in a fasting state and lipid profile was detected 24 . As most studies have been performed on laboratory animals,16, 25, 26, 27, 28, 29, 30 and due to lack of comparison on the rate of effectiveness of the different doses of this plant on patients with diabetes type II as well as controversial outcomes of the studies, it is essential to compare the effectiveness of the different doses of green cumin extract. Therefore, the present study was designed for the purpose of evaluating the effect of 50 and 100 mg doses of essential oil of C. cyminum on the glycemic indices and some inflammatory indices (TNF-α, adiponectin and hsCRP) in patients with diabetes type II.…”
Section: Introductionmentioning
confidence: 95%
“…This plant has antioxidant properties and it has been used in traditional medicine as a stimulant, carminative, and coagulant 15 . Studies on laboratory animals have shown that essential oil of C. cyminum has anti-diabetic properties 16 . The effective components of this plant are Cumin aldehyde, γ-Terpinine, α-Sabinin, α-Flandren and α-Kadinin, 17 of which Cuminaldehyde or 4-Isopropil Benzaldhyde is the most effective.…”
Section: Introductionmentioning
confidence: 99%